Commodity Market Risk as a Determinant of Corporate R&D Investment - Konrad SZYDŁOWSKI (Communications of International Proceedings, 2025)
The article addresses the problem of corporate R&D investment in the conditions of commodity market risk. The research goal was to determine the importance of the volatility of crude oil prices as a determinant of corporate R&D expenditures. The analysis was conducted on a group of companies representing the oil industry. Research showed that the volatility of oil prices is an important determinant of the financial condition of R&D investment. The decline in oil prices led to reduced profitability and financial liquidity, indicating a deterioration in the financial condition of the analyzed companies. Simultaneously, an increase in R&D investments was observed. The opposite effect was identified during periods of growth. These trends were particularly clear in subperiods of dynamic trends in oil market.
Keywords: commodity market risk; R&D.